Overpowering the law enforcing agency and human rights challenges - Ullah, AKM Ahsan; Sagor, Lutfunnessa (Border Crossing, 2018)
This research seeks to explore and understand the extent of human rights is violated by an elite force in Bangladesh. The constitutional right to life should not be derogated or suspended, and no person should be stripped of his or her basic human rights. (Number) of victims and human rights activists were recruited via snowball sampling and in-depth interviews were conducted. Secondary data was obtained via daily newspapers, magazines and bulletins published by various human rights organizations in Bangladesh. This is due to the elite force ignoring the existing constitutional guarantee of the right to life. The participants views were that the government has to ensure human rights are maintained. It should limit the jurisdiction of the elite force and conform to the Universal Declaration of Human Rights.